Insight into the Origin of Multiwavelength Emissions of PKS 1510−089 Through Modeling 12 SEDs from 2008 to 2015 - Maichang Lei; Yuan Zheng; Jianfu Zhang; Yuhai Yuan; Jiancheng Wang (The Astrophysical Journal)
PKS 1510−089 is one of the most peculiar sources among the flat spectrum radio quasars, exhibiting a notable big blue bump. This provides a unique opportunity to explore the coupling between the activity of the central engine and the relativistic jet, offering further insight into the origin of the multiwavelength emissions. To this end, we collected multiwavelength data spanning four periods from 2008 to 2015 and performed the spectral energy distribution (SED) modeling using a one-zone homogeneous leptonic model. In the model, a multichromatic accretion disk (AD) is used to fit the optical/UV data sets, while the external radiation fields from the broad-line region (BLR) and dusty torus (DT) are properly considered to produce the high-energy γ -ray emissions. Our best fit to 12 SEDs yields the following results: (i) The innermost stable orbit ( R _ISO ) of the AD is not stable but varies between 3 R _S and 18 R _S during these observations. (ii) The high-energy hump of the SED is well dominated by Compton scattering of the BLR photons, while the X-ray flux may be comprised of multiple radiation components. (iii) The γ -ray emitting regions are generally matter-dominated, with low magnetization, and are located beyond the BLR but within the DT. At such distance, the multiwavelength emissions are likely to originate from shock accelerations. (iv) For the energization of the relativistic jet, our study supports the Blandford−Znajek mechanism, instead of the Blandford−Payne mechanism, as the latter fails to power the jet.